2021
DOI: 10.1590/1678-6971/eramr210083
|View full text |Cite
|
Sign up to set email alerts
|

Absorptive Capacity, Innovation, and External Sources of Knowledge: The Brazilian Power Sector

Abstract: Purpose: This paper discusses the relationship between absorptive capacity, external sources of knowledge, and innovation in the context of the power sector. In doing so, we follow the theoretical debate over absorptive capacity dimensions. We focus on the statistical testing of Zahra and George’s (2002) absorptive capacity construct to identify whether their dimensions find support in reality. We consider that the external environment encompasses both scientific and industrial sources of knowledge, which infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
(92 reference statements)
0
2
0
2
Order By: Relevance
“…In their studies, the Cronbach's alpha, AVE, and CR for all constructs are in the range between 0.717 to 0.936, 0.514 to 0.633, and 0.842 to 0.991, respectively. A study conducted to assess absorptive capacity, external sources of knowledge and innovation in the Brazilian power sector also found that Cronbach's alpha, AVE, and CR for the four dimensions of absorptive capacity were in the range between 0.84 to 0.87, 0.55 to 0.66, 0.88 to 0.91 respectively (Versiani et al, 2021). Similarly, another study conducted among Chinese high-tech firms to assess the effect of absorptive capacity and innovative culture on job performance and found the value of Cronbach's alpha, AVE, and CR for the four dimensions of absorptive capacity, innovative culture, and innovative performance respectively in the range between 0.904 to 0.931, 0.657 -0.732, 0.905 to 0.932.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In their studies, the Cronbach's alpha, AVE, and CR for all constructs are in the range between 0.717 to 0.936, 0.514 to 0.633, and 0.842 to 0.991, respectively. A study conducted to assess absorptive capacity, external sources of knowledge and innovation in the Brazilian power sector also found that Cronbach's alpha, AVE, and CR for the four dimensions of absorptive capacity were in the range between 0.84 to 0.87, 0.55 to 0.66, 0.88 to 0.91 respectively (Versiani et al, 2021). Similarly, another study conducted among Chinese high-tech firms to assess the effect of absorptive capacity and innovative culture on job performance and found the value of Cronbach's alpha, AVE, and CR for the four dimensions of absorptive capacity, innovative culture, and innovative performance respectively in the range between 0.904 to 0.931, 0.657 -0.732, 0.905 to 0.932.…”
Section: Discussionmentioning
confidence: 97%
“…Studies on the creation of new services or products, adoption of novel technology, the dissemination of technology-related knowledge, and organizational learning have all examined how an absorptive capacity affects individual/organization performance (Schweisfurth & Raasch, 2018). Instead of using a direct measure to assess absorptive capacity, the majority of research employs proxies such as the number of scientists, the training of R & D members, R & D spending, or a combination of any of these facets (Versiani, Cruz, Rezende, & Castro, 2021). Additionally, numerous studies have assessed how the absorptive capacity at the organizational level influences its performance (García-Sánchez, García-Morales, & Martín-Rojas, 2018; Sancho-Zamora, Hernández-Perlines, Peña-García, & Gutiérrez-Broncano, 2022).…”
Section: Absorptive Capacity For E-learning and Job Performancementioning
confidence: 99%
“…W niektórych pracach akcentuje się pozytywne oddziaływanie kultury organizacyjnej na efektywność poprzez poprawę postrzegania innowacji o charakterze organizacyjnym (Azeem i in., 2021;Naveed i in., 2022). W innych dostrzega się zależność skuteczności wdrażania innowacji opartych na źródłach zewnętrznych (innowacji otwartych) od rodzaju kultury organizacyjnej panującej w danej firmie (Scaliza i in., 2022), choć znaczenie ma tu także zdolność absorpcyjna powiązana z charakterem źródeł wiedzy (Versiani i in., 2021). Jak piszą AlQershi i in.…”
Section: Innowacjeunclassified
“…Dotyczy to m.in. tych przywoływanych wcześniej prac, których autorzy doceniają wagę kultury organizacyjnej (Azeem i in., 2021;Naveed i in., 2022;Scaliza i in., 2022;Versiani i in., 2021) Innowacja często wymaga informacji i wiedzy, których nie ma w ramach organizacji. Wymóg ten motywuje menedżerów do poszukiwania zewnętrznych źródeł wiedzy i importowania nowej wiedzy do organizacji (Mol i Birkinshaw, 2009).…”
Section: Wnioski I Dyskusjaunclassified
“…Thus, many organizations face challenges in benefiting from external knowledge flows, even those with easily accessible information sources (Cassiman & Veugelers, 2006;Escribano et al, 2009). Versiani et al, (2021) explored absorptive capacity and external knowledge sources in their study. They highlight the relationship between external knowledge and innovation, noting that few studies explore the relationship between external and internal factors on innovation performance.…”
Section: Introductionmentioning
confidence: 99%